Advances in pharmacotherapy for cardiac amyloidosis. (4th March 2021) - Spoladore, R.; Falasconi, G.; Marcatti, M.; Di Maio, S.; Fiore, G.; Slavich, M.; Margonato, A.; Turco, A.; Fragasso, G.
ABSTRACT: Introduction: Amyloidosis is a group of progressive and devastating disorders resulting from extracellular deposition of misfolded proteins into tissues. When deposition of fibrils occurs in cardiac tissues, this systemic disease can lead to a very poor prognosis. Systemic amyloidosis can be acquired [light chain (AL) amyloidosis; AA amyloidosis], or hereditary [transthyretin (ATTR) amyloidosis]. Cardiac disease in amyloidosis is usually secondary to a systemic disease. The diagnosis of cardiac involvement is often delayed and yields an adverse prognosis. Areas covered: in this review, the authors report current literature on advances in pharmacotherapy for cardiac amyloidosis, mainly focused on AL and ATTR amyloidosis treatment. Expert opinion: Most pharmacological trials in amyloidosis patients, both AL and TTR, are directed to study the effects of drugs on polyneuropathy. However, since cardiac involvement carries a prominent negative survival impact in amyloidosis patients, future research should be more focused on amyloidosis cardiomyopathy as primary endpoint. Additionally, in AL amyloidosis therapies are mainly derived from experience on multiple myeloma treatment. In this specific setting, possible future research could particularly focus on immunotherapeutic agents able to optimize the standard chemotherapy results and, thus, allowing a larger population of patients to be treated by bone marrow stem cell transplantation.